Apoptosis and Its Significance in Oral Diseases: An Update. (15th December 2013) - Jain, Megha; Kasetty, Sowmya; Udyavara Sridhara, Sudheendra; Jain, Nitin; Khan, Samar; Desai, Ami
Abstract : Apoptosis is a well defined mode of cell death which plays an imperative role in the development, regulation, and maintenance of the cell populations in multicellular organisms. Apoptosis is implicated in both health and diseases. Errors in apoptotic mechanisms have been allied to a wide range of pathologies including oral diseases. This review presents an update focused on the role and significance of apoptosis in various oral diseases ranging from reactive to benign and malignant pathologies.